Effectiveness of Digital Media in Health Promotion Campaigns: A Literature Study - Nurmidin, M Fadhel; Surya, Welong S. (Jurnal Kesmas Prima Indonesia, 2025)
The advancement of the digital era has created great opportunities to support health promotion through social media. This study aims to analyze the effectiveness of digital media, especially social media platforms, in disseminating health information while encouraging healthier behavior changes. The study used a literature review method by reviewing various trusted sources published between 2019 and 2024. The results show that social media has several advantages, such as the ability to reach a broad audience, high interactivity, content that can be tailored to needs, and ease in evaluating campaign success. In conclusion, social media shows significant potential as a health promotion tool. This study recommends a combination of digital and traditional strategies to maximize campaign results and the need for further research to assess the long-term impact of digital-based health promotion. Keywords: Digital Media, Health Promotion, Social Media